THE EFFECT OF APPLYING THINK-PAIR-SHARE ON THE STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT AT VIII GRADE STUDENTS OF SMP NEGERI 32 MEDAN - Simamora, Binaria Juliana; Ginting, Fiber Yun Almanda; Lumbanraja, Bogor; Prayuda, Meikardo Samuel; Siahaan, Junita (Jurnal Ilmiah Aquinas, 2025)
This study investigates the effect of applying the Think-Pair-Share (TPS) strategy on students’ reading comprehension of descriptive texts among eighth-grade students at SMP Negeri 32 Medan. The research was motivated by observations that students struggled with reading comprehension due to monotonous teaching methods that lacked student engagement. Using an experimental design, the study involved two groups: the experimental group was taught using the TPS strategy, while the control group received conventional instruction. Both groups completed a pre-test and post-test comprising multiple-choice questions focused on descriptive texts. The results revealed a significant improvement in the reading comprehension scores of students in the experimental group. The mean score of the experimental group increased from 48.5 in the pre-test to 78.625 in the post-test, whereas the control group showed only a slight improvement, from 56.25 to 58.75. Statistical analysis using a paired sample t-test confirmed the effectiveness of the TPS strategy in enhancing students’ reading comprehension. These findings suggest that the TPS strategy is a beneficial approach for improving student engagement and comprehension in reading, particularly for descriptive texts.